High-strength nano baked porcelain metal plate and preparation method thereof

By performing anode modification on the substrate of the porcelain metal plate and forming the mesh structure of the porcelain layer, the problems of substrate defects and low adhesion are solved, the strength and adhesion of the plate are improved, and the tensile resistance is significantly improved Strength and impact resistance.

CN119281627AActive Publication Date: 2025-01-10CHONGQING HENGYA ALUMINUM CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411211695.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The substrates of existing porcelain metal plates have defects such as cracks and pores, and the adhesion between the porcelain layer and the substrate is relatively low, which affects the strength and service life of the plate.

Method used

By using the metal plate substrate as an anode, it is powered on in a mixed solution containing methacrylate and fluorocarbon surfactant to form polymer-filled surface gaps or pores of the substrate and use silicon dioxide in the porcelain layer Materials such as powder, alumina powder, etc. form a mesh structure to enhance adhesion.

Benefits of technology

The strength of the metal plate substrate and the adhesion of the porcelain layer to the substrate are improved, and the tensile strength and impact resistance of the plate are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281627A_ABST
    Figure CN119281627A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building curtain walls, and discloses a high-strength nano baked porcelain metal plate and a preparation method of the high-strength nano baked porcelain metal plate. The preparation method comprises the following steps: simultaneously inserting an anode and a cathode into a mixed solution containing methacrylate and a fluorocarbon surfactant, switching on a direct-current power supply to modify a metal plate base material, coating a baked porcelain layer on the modified metal plate, curing the baked porcelain layer on the metal plate coated with the baked porcelain layer at 150-280 DEG C, and cooling to obtain the high-strength nano baked porcelain metal plate. The polymer is formed on the surface and pores / gaps of the metal plate base material through an anode modification method, the effect of protecting and filling the gaps or pores in the surface of the metal plate base material is achieved, and the strength of the metal plate base material is improved; and the polymer on the surface of the metal plate base material is provided with a layer of carboxylate radical ions, so that the polymer and silicon and aluminum in the baked porcelain layer material can form silicon-oxygen bonds and aluminum-oxygen bonds with net structures, and the adhesive force between the baked porcelain layer and the metal plate base material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building curtain walls and discloses a high-strength nano-porcelain metal plate and a preparation method thereof. Background Art

[0002] Porcelain metal plate is a curtain wall decorative plate formed by spraying inorganic water-based ceramic coating on a metal plate substrate and curing it after baking. It has the characteristics of high temperature resistance, non-flammability, smoke-free, high hardness, easy to clean, safe and environmentally friendly, energy-saving, etc. In recent years, it has been used more and more widely in public places such as subway stations, tunnels, high-speed railway stations, airports, hospitals, and schools. However, the substrate used to process the porcelain metal plate may have defects such as cracks and pores, and the existing porcelain metal plate also has a problem of low adhesion to the porcelain material. In the prior art, the metal plate substrate is often subjected to pre-treatment processes such as sandblasting before the porcelain metal plate is processed, which increases the contact area between the porcelain layer and the substrate, thereby increasing the adhesion between the porcelain layer and the substrate, but this will further deepen the growth of cracks or pores on the surface of the substrate, which has an adverse effect on the strength of the porcelain metal plate. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength nano-ceramic metal plate and a preparation method thereof, which not only protects and fills the surface gaps or pores of the metal plate substrate, improves the strength of the metal plate substrate, but also helps to improve the adhesion between the porcelain layer and the metal plate substrate.

[0004] In order to achieve the above technical effects, the technical solution adopted by the present invention is:

[0005] A method for preparing a high-strength nano-ceramic metal plate, comprising:

[0006] dissolving methacrylate in water, and adding a fluorocarbon surfactant to the methacrylate solution to form a mixed solution;

[0007] Using a metal plate substrate as an anode and a conductive material as a cathode, inserting the anode and the cathode into the mixed solution at the same time and connecting a direct current power supply for more than 20 minutes to obtain a modified metal plate;

[0008] Coating a porcelain layer on the modified metal plate, wherein the porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water;

[0009] The metal plate coated with the porcelain layer is cured at 150-280° C., and a high-strength nano-porcelain metal plate is obtained after cooling.

[0010] Furthermore, the metal plate substrate is an aluminum plate, an aluminum alloy plate or a stainless steel plate.

[0011] Furthermore, the methacrylate is a combination of one or more of potassium methacrylate, sodium methacrylate, and zinc methacrylate, and the fluorocarbon surfactant is a cationic fluorocarbon surfactant or an amphoteric fluorocarbon surfactant; wherein the molar concentration of methacrylate in the mixed solution is 0.2 to 0.6 mol / L, and the molar concentration of the fluorocarbon surfactant in the mixed solution is 0.04 to 0.08 mol / L.

[0012] Furthermore, the current provided by the DC power supply is 2-6 mA.

[0013] Furthermore, the porcelain layer includes, by weight, 2 to 6 parts of silicon dioxide powder, 0.2 to 3 parts of aluminum oxide powder, 25 to 40 parts of tetraethoxysilane, 25 to 40 parts of tetraisopropoxysilane, 36 to 60 parts of isopropanol, and 50 to 80 parts of water.

[0014] Furthermore, the step of coating a porcelain layer on the modified metal plate comprises:

[0015] Premixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol, and water to form a first mixture;

[0016] After the first mixed material is kept at 80±5°C for 2 to 10 hours, isopropyl alcohol is added to the first mixed material for dilution, and the mixture is stirred evenly to form a ceramic layer coating;

[0017] The coating is coated on the modified metal plate by spin coating or spray coating.

[0018] In order to achieve the above technical effects, the present invention also provides a high-strength nano-ceramic metal plate, comprising:

[0019] A modified metal plate substrate, wherein the modified metal plate substrate is obtained by using a metal plate as an anode material and performing electrical modification in a mixed solution containing methacrylate and a fluorocarbon surfactant;

[0020] The porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water, and is obtained by heat preservation and curing at 150-280°C.

[0021] The metal plate substrate is an aluminum plate, an aluminum alloy plate or a stainless steel plate.

[0022] Furthermore, the methacrylate is a combination of one or more of potassium methacrylate, sodium methacrylate, and zinc methacrylate, and the fluorocarbon surfactant is a cationic fluorocarbon surfactant or an amphoteric fluorocarbon surfactant; wherein the molar concentration of methacrylate in the mixed solution is 0.2 to 0.6 mol / L, and the molar concentration of the fluorocarbon surfactant in the mixed solution is 0.04 to 0.08 mol / L.

[0023] Furthermore, the porcelain layer includes 2 to 6 parts of silicon dioxide powder, 0.2 to 3 parts of aluminum oxide powder, 25 to 40 parts of tetraethoxysilane, 25 to 40 parts of tetraisopropoxysilane, 36 to 60 parts of isopropanol, and 50 to 80 parts of water.

[0024] Compared with the prior art, the present invention has the following beneficial effects: the present invention forms a polymer on the surface and pores / crevices of the metal plate substrate by an anodic modification method, which plays a role in protecting and filling the crevices or pores on the surface of the metal plate substrate, thereby improving the strength of the metal plate substrate; and the polymer on the surface of the metal plate substrate carries a layer of carboxylate ions, which helps to form a network structure of silicon-oxygen bonds and aluminum-oxygen bonds with silicon and aluminum in the porcelain layer material, thereby improving the adhesion between the porcelain layer and the metal plate substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a flow chart of the preparation method of the high-strength nano-ceramic metal plate in Example 1 or 2. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the embodiments and drawings. However, it should not be understood that the scope of the above subject matter of the present invention is limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.

[0027] Example 1

[0028] See also Figure 1 , a method for preparing a high-strength nano-ceramic metal plate, comprising:

[0029] dissolving methacrylate in water, and adding a fluorocarbon surfactant to the methacrylate solution to form a mixed solution;

[0030] Using a metal plate substrate as an anode and a conductive material as a cathode, inserting the anode and the cathode into the mixed solution at the same time and connecting a direct current power supply for more than 20 minutes to obtain a modified metal plate;

[0031] Coating a porcelain layer on the modified metal plate, wherein the porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water;

[0032] The metal plate coated with the porcelain layer is cured at 150-280° C., and a high-strength nano-porcelain metal plate is obtained after cooling.

[0033] In this embodiment, a metal plate substrate is used as an anode material and a conductive material is used as a cathode material. After the anode material and the cathode material are simultaneously immersed in a mixed solution containing methacrylate and a fluorocarbon surfactant and energized, the metal plate substrate of the anode is positively charged, which can attract methacrylate ions and fluorocarbon groups to move toward the anode, not only allowing the methacrylate ions and fluorocarbon groups to adhere to the surface of the metal plate substrate, but also allowing the methacrylate ions to penetrate into the surface gaps or pores of the metal plate substrate under the action of charge attraction. When the power is continuously turned on, the cathode generates The electrons also continue to move toward the anode through the solution, bombarding the methacrylate ions attached to the surface of the metal plate substrate and infiltrated into the gaps or pores, causing the carbon-carbon double bonds in the methacrylate to break, and polymerize on the surface of the metal plate substrate and in the pores / gaps to form polymers, which play a role in protecting and filling the gaps or pores on the surface of the metal plate substrate, thereby improving the strength of the metal plate substrate; the polymer on the surface of the metal plate substrate carries a layer of carboxylate ions, which helps to form a network structure of silicon-oxygen bonds and aluminum-oxygen bonds with silicon and aluminum in the porcelain layer material, thereby improving the adhesion between the porcelain layer and the metal plate substrate. In addition, the fluorocarbon surfactant in the mixed solution can not only improve the wettability of methacrylate ions on the surface of the metal plate, allowing the methacrylate ions to contact the surface of the metal plate and increase the adhesion area of ​​the methacrylate ions to the metal plate; in addition, the radius of the fluorine ions in the fluorocarbon organic matter is small, and after being attracted by the anode metal plate, the fluorine ions can better penetrate under the surface of the metal plate, and under the strong electronegativity of the fluorine ions, the organic groups on the exposed metal surface are positively charged, which can enhance the binding ability of the fluorocarbon organic compound with the methacrylate ions, thereby further enhancing the adhesion between the porcelain layer and the metal plate substrate, and the free fluorine ions in the mixed solution can act as halogen elements to promote the breaking of carbon-carbon double bonds, which further promotes the polymerization of methacrylate ions on the surface of the metal plate substrate and in the pores / crevices to form polymers.

[0034] Based on the same inventive concept, this embodiment also provides a high-strength nano-ceramic metal plate, including:

[0035] A modified metal plate substrate, wherein the modified metal plate substrate is obtained by using a metal plate as an anode material and performing electrical modification in a mixed solution containing methacrylate and a fluorocarbon surfactant;

[0036] The porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water, and is obtained by heat preservation and curing at 150-280°C.

[0037] The metal plate substrate in this embodiment is an aluminum plate, an aluminum alloy plate or a stainless steel plate.

[0038] The methacrylate is one or more of potassium methacrylate, sodium methacrylate and zinc methacrylate, and the fluorocarbon surfactant is a cationic fluorocarbon surfactant or an amphoteric fluorocarbon surfactant.

[0039] In order to ensure that the polymer on the surface of the metal plate substrate can be stably formed, the current provided by the DC power supply is controlled to be 2-6 mA in this embodiment.

[0040] Example 2

[0041] See also Figure 1 , a method for preparing a high-strength nano-ceramic metal plate, comprising:

[0042] Step 1, dissolving methacrylate in water, and adding a fluorocarbon surfactant to the methacrylate solution to form a mixed solution;

[0043] In this embodiment, sodium methacrylate and quaternary ammonium cationic fluorocarbon surfactant are used as raw materials to prepare a mixed solution, and the molar concentration of methacrylate in the prepared mixed solution is 0.3 mol / L, and the molar concentration of the fluorocarbon surfactant is 0.05 mol / L.

[0044] Step 2: Using a 2.0 mm thick aluminum alloy plate substrate as an anode and a carbon rod as a cathode, inserting the anode and cathode into the mixed solution at the same time and connecting a DC power supply for 120 min to obtain a modified metal plate; in this embodiment, the current provided by the DC power supply is 5 mA.

[0045] Step 3, premix 4 parts of silicon dioxide powder, 1.5 parts of aluminum oxide powder, 30 parts of tetraethoxysilane, 30 parts of tetraisopropoxysilane, 15 parts of isopropanol, and 55 parts of water to form a first mixture;

[0046] Step 4, after the first mixture is kept at 80±5°C for 8 hours, 30 parts of isopropanol are added to the first mixture, and the mixture is stirred evenly to form a ceramic layer coating;

[0047] Step 5: Apply the coating on the modified metal plate by spraying; in this embodiment, the spraying thickness is controlled to be 0.05-0.12 mm;

[0048] Step 6: Curing the ceramic layer of the metal plate coated with the ceramic layer at 150-280° C., and obtaining a high-strength nano-ceramic metal plate after cooling.

[0049] In this embodiment, an aluminum alloy plate substrate of the same model and size is taken, and the method of steps 3 to 6 is directly used to prepare a porcelain metal plate to obtain a comparative sample, which is used for performance test comparison with the high-strength nano-porcelain metal plate in steps 1 to 6; the test items are:

[0050] Thickness of porcelain layer: Measure in accordance with the provisions of GB / T4957. The local film thickness at least at the four corners and the center of each sample shall be measured.

[0051] Tensile strength: Measure according to the tensile strength test procedures for thin plate specimens with a thickness of 0.1 to 3 mm in Appendix B of GB / T228.1.

[0052] Impact resistance: The test is carried out in accordance with the provisions of GB / T1732. The weight of the impact hammer is 1000g±1g, the punch diameter is 15.9mm±0.3mm, the porcelain decorative surface of the sample faces upward, and the maximum impact height at which no cracks, wrinkles or peeling of the porcelain decorative surface are observed is measured.

[0053] Dry adhesion: Carry out the cross-cut test according to the provisions of GB / T9286, where the cross-cut spacing of the porcelain layer is 1mm. Cover the cross-cut coating with a tape of 25mm width and an adhesive force of (10±1)N / 25mm, drive out the air under the tape, quickly pull the tape apart vertically, and observe it with an AM413ZT digital microscope after magnifying it 200 times, and observe the shedding of the porcelain layer in each grid.

[0054] The relevant test data of the high-strength nano-ceramic metal plate prepared in this embodiment and the comparative sample are shown in Table 1 below:

[0055] Table 1 Performance data comparison table of porcelain metal plate samples

[0056]

[0057] The above-mentioned relevant test data show that the tensile strength and impact resistance of the high-strength nano-ceramic metal plate made of anodically modified aluminum alloy plates are improved, and the adhesion between the ceramic layer and the substrate is also significantly improved.

[0058] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-strength nano-ceramic metal plate, characterized in that: include: dissolving methacrylate in water, and adding a fluorocarbon surfactant to the methacrylate solution to form a mixed solution; Using a metal plate substrate as an anode and a conductive material as a cathode, inserting the anode and the cathode into the mixed solution at the same time and connecting a direct current power supply for more than 20 minutes to obtain a modified metal plate; Coating a porcelain layer on the modified metal plate, wherein the porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water; The metal plate coated with the porcelain layer is cured at 150-280° C., and a high-strength nano-porcelain metal plate is obtained after cooling.

2. The method for preparing a high-strength nano-ceramic metal plate according to claim 1, characterized in that: The metal plate substrate is an aluminum plate, an aluminum alloy plate or a stainless steel plate.

3. The method for preparing a high-strength nano-ceramic metal plate according to claim 1, characterized in that: The methacrylate is one or more combinations of potassium methacrylate, sodium methacrylate, and zinc methacrylate; the fluorocarbon surfactant is a cationic fluorocarbon surfactant or an amphoteric fluorocarbon surfactant; wherein the molar concentration of methacrylate in the mixed solution is 0.2 to 0.6 mol / L, and the molar concentration of the fluorocarbon surfactant in the mixed solution is 0.04 to 0.08 mol / L.

4. The method for preparing a high-strength nano-ceramic metal plate according to claim 1, characterized in that: The current provided by the DC power supply is 2 to 6 mA.

5. The method for preparing a high-strength nano-ceramic metal plate according to claim 1, characterized in that: In parts by weight, the porcelain layer comprises 2 to 6 parts of silicon dioxide powder, 0.2 to 3 parts of aluminum oxide powder, 25 to 40 parts of tetraethoxysilane, 25 to 40 parts of tetraisopropoxysilane, 36 to 60 parts of isopropanol, and 50 to 80 parts of water.

6. The method for preparing a high-strength nano-ceramic metal plate according to claim 5, characterized in that: The steps of coating the ceramic layer on the modified metal plate include: Premixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol, and water to form a first mixture; After the first mixed material is kept at 80±5°C for 2 to 10 hours, isopropyl alcohol is added to the first mixed material for dilution, and the mixture is stirred evenly to form a ceramic layer coating; The coating is coated on the modified metal plate by spin coating or spray coating.

7. A high-strength nano-ceramic metal plate, characterized in that: include: A modified metal plate substrate, wherein the modified metal plate substrate is obtained by using a metal plate as an anode material and performing electrical modification in a mixed solution containing methacrylate and a fluorocarbon surfactant; The porcelain layer is mainly formed by mixing silicon dioxide powder, aluminum oxide powder, tetraethoxysilane, tetraisopropoxysilane, isopropanol and water, and is obtained by heat preservation and curing at 150-280°C. The metal plate substrate is an aluminum plate, an aluminum alloy plate or a stainless steel plate.

8. The high-strength nano-ceramic metal plate according to claim 7, characterized in that: The methacrylate is one or more combinations of potassium methacrylate, sodium methacrylate, and zinc methacrylate; the fluorocarbon surfactant is a cationic fluorocarbon surfactant or an amphoteric fluorocarbon surfactant; wherein the molar concentration of methacrylate in the mixed solution is 0.2 to 0.6 mol / L, and the molar concentration of the fluorocarbon surfactant in the mixed solution is 0.04 to 0.08 mol / L.

9. The high-strength nano-ceramic metal plate according to claim 7, characterized in that: The porcelain layer comprises 2-6 parts of silicon dioxide powder, 0.2-3 parts of aluminum oxide powder, 25-40 parts of tetraethoxysilane, 25-40 parts of tetraisopropoxysilane, 36-60 parts of isopropanol and 50-80 parts of water.

Citation Information

Patent Citations

  • Physical pretreatment and electrophoresis coating process of aluminum magnesium alloy

    CN101967667A

  • Electropolymerization of a coating onto an electrode material

    CN104937146A

  • Coating for skis and snowboards contains polyions of a polyelectrolyte and oppositely-charged ions of an ionic fluorinated surfactant in the form of a complex in the coating

    DE19901973A1

  • Inorganic paints composition

    KR1020050069215A

  • Electropolymerization of a coating onto an electrode material

    US20140173889A1